2003
DOI: 10.1161/01.cir.0000087605.09362.0e
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Percutaneous Transluminal Coronary Angioplasty and Medical Therapy in Stable Survivors of Acute Myocardial Infarction With Single Vessel Disease

Abstract: Background-Percutaneous transluminal coronary angioplasty of the infarct-related artery in stable survivors of acute myocardial infarction is often performed, even in patients without any symptoms or residual ischemia. Despite the lack of randomized studies, it is widely believed that this intervention will improve the clinical outcome of these patients. Methods and Results-Three hundred patients with single vessel disease of the infarct vessel and no or minor angina pectoris in the subacute phase (1 to 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 31 publications
(19 reference statements)
2
45
0
5
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] For the BARI 2D trial, we included the PCI stratum of the trial only. The trials enrolled a total of 8070 patients who were followed up for a mean of 5.0 years (range, 1.5-10.2 years) with 37 548 patient-years of follow-up.…”
Section: Study Selectionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] For the BARI 2D trial, we included the PCI stratum of the trial only. The trials enrolled a total of 8070 patients who were followed up for a mean of 5.0 years (range, 1.5-10.2 years) with 37 548 patient-years of follow-up.…”
Section: Study Selectionmentioning
confidence: 99%
“…42 Whether routine delayed angioplasty (regardless of the presence of symptoms or ischemia) within days to weeks of fibrinolysis in stable patients would be beneficial was tested in 6 trials in the balloon angioplasty era. [43][44][45][46][47][48][49] In the largest of these studies, the TIMI-II trial, 3262 patients treated with recombinant tissue plasminogen activator within 4 hours of STEMI onset were randomized to coronary arteriography 18 to 48 hours after fibrinolysis with routine balloon angioplasty if the coronary anatomy was suitable or to angiography and revascularization only in patients with spontaneous or exercise-induced ischemia. The rates of death or reinfarction in the invasive and conservative groups were similar at 42 days (11.1% and 10.1%; Pϭ0.31) and 1 year (14.7% and 15.2%; Pϭ0.…”
Section: Delayed Routine and Selective Angioplastymentioning
confidence: 99%
“…43,44 Three other trials confirmed these results, [45][46][47] 48 and another showed reduced rates of readmission for severe angina and unplanned revascularization procedures with the invasive approach. 49 One reason these early trials of routine delayed angioplasty may have been negative was the enrollment of patients regardless of whether myocardial ischemia and/or viability were present. In the Danish Trial in Acute Myocardial Infarction (DANAMI) trial, 1008 patients with inducible ischemia after fibrinolysis (Ͼ99% streptokinase) for a first STEMI were randomized to conservative care or to catheterization followed by revascularization with balloon angioplasty or coronary artery bypass graft surgery when appropriate.…”
Section: Delayed Routine and Selective Angioplastymentioning
confidence: 99%
“…Alguns registros já apontam para possível benefício da revascularização nos dias ou semanas iniciais após IAM 216;217 . Nos últimos anos, diferentes estudos demonstraram benefício com a revascularização tardia de pacientes estáveis pós-infarto [218][219][220] .…”
Section: -Cinecoronariografiaunclassified
“…Essas foram as conclusões do ALKK (Arbeitsgemeinschaft Leitender Kardiologischer Krankenhausarzte) 219 , uma série comparativa e randomizada com o tratamento clínico, realizada na Alemanha.…”
Section: Procedimento -Intervenção Coronária Percutânea Primáriaunclassified